ANALYSIS OF CHARACTER VALUES IN THE POETRY OF "LETTER FROM MOTHER" WORKS ASRUL SANI AND "UNKNOWN HEROES" WORKS TOTO SUDARTO BACHTIAR - Rokhmaniyah Rokhmaniyah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
This article describes the results of a study based on the importance of character education for the younger generation, especially children. This is due to the fact that the character of the nation is decreasing. For this reason, a research was conducted which aimed to analyze the values of the characters found in the poem "Letter from Mother" by Asrul Sani and "Unknown Heroes" by Toto Sudarto Bachtiar. It is expected that the results of the research can be used by teachers to build the character of their students through classroom learning. This research is literature research with data collection techniques through literature study which contains both poems. Data collection tool using poetry study sheet. The source of this research is poetry and dictionary texts (Large Indonesian Dictionary), as well as experts. To maintain data validity, source triangulation techniques are used. The results showed the character values contained in the poem "Letter from Mother" and "Unknown Hero". Character values are implied in the poetry "Surat dari Ibu" by Asrul Sani and poetry"Unknown Heroes" by Toto Sudarto Bachtiar, namely: independent, nationalist and integrity